Intracellular compartment-specific proteasome dysfunction in postmortem cortex in schizophrenia subjects - Scott, Madeline R; Meador-Woodruff, James H (Molecular psychiatry, 2020)
Protein homeostasis is an emerging component of schizophrenia (SZ) pathophysiology. Proteomic alterations in SZ are well-documented and changes in transcript expression are frequently not associated with changes in protein expression in SZ brain. The underlying mechanism driving these changes remains unknown, though altered expression of ubiquitin proteasome system (UPS) components have implicated protein degradation. Previous studies have been limited to protein and transcript expression, however, and do not directly test the function of the proteasome. To address this gap in knowledge, we measured enzymatic activity associated with the proteasome (chymotrypsin-, trypsin-, and caspase-like) in the superior temporal gyrus (STG) of 25 SZ and 25 comparison subjects using flourogenic substrates. As localization regulates which cellular processes the proteasome contributes to, we measured proteasome activity and subunit expression in fractions enriched for nucleus, cytosolic, and membrane compartments. SZ subjects had decreased trypsin-like activity in total homogenate. This finding was specific to the nucleus-enriched fraction and was not associated with changes in proteasome subunit expression. Interestingly, both chymotrypsin-like activity and protein expression of 19S RP subunits, which facilitate ubiquitin-dependent degradation, were decreased in the cytosol-enriched fraction of SZ subjects. Intracellular compartment-specific proteasome dysfunction implicates dysregulation of protein expression both through altered ubiquitin-dependent degradation of cytosolic proteins and regulation of protein synthesis due to degradation of transcription factors and transcription machinery in the nucleus. Together, these findings implicate proteasome dysfunction in SZ, which likely has a broad impact on the proteomic landscape and cellular function in the pathophysiology of this illness.